PENGARUH KEMAMPUAN BERPIKIR TERHADAP PENGUASAAN KONSEP DAN HASIL BELAJAR SISWA - Eko Meinanto; I Dewa Putu Nyeneng; Nengah Maharta (Jurnal Pembelajaran Fisika, 2013)
Physics teachers have used the approach to the material process skills using practical. However, the physics student learning outcomes is still relatively low. This is due to the observed process skills are less complex. So the results of their study was still relatively low. This study aimed to determine (1) The effect of the ability to think on mastery of concepts students with the skills approach, (2) The effect of the ability to think on learning outcomes of students' learning process skills approach. This research was conducted in the classroom VII5 School 1 Pekalongan are 32 students in the semester of the school year 2012/2013 with the material sub Heat. The sampling technique used is purposive sampling. The design of this study is the One-Shot Case Study. Based on this study, the data obtained thinking skills, mastery of concepts and learning result are then analyzed using linear regression with SPSS 17.0. The analysis showed that the three data were normally distributed and linear. Furthermore, to examine the effect done by correlation test and simple linear regression with SPSS 17.0. The results of this study show that: (1) There is the influence of the ability to think on mastery of concepts students with the skills approach. and (2) There is the influence of the ability to think on learning outcomes process skills approach.Keywords: thinking skills, process skills approach, mastery concepts, learning result.